Penyuluhan Dan Pelayanan Keluarga Berencana Pada Pasangan Usia Subur Di Desa Sendayan - Hamidah Sari,; Andriani, Andriani; Suryani, Linda; Hartian, T.; Hana Harahap, Mustika; Mulyani, Siska (COVIT (Community Service of Tambusai), 2023)
: Family planning is a program launched by the government, with the aim of planning pregnancy, so that pregnancy occurs at the desired time. Where the distance between births is extended and subsequent births can be prevented if the number of children is reached as desired, to foster the health of all family members as well as possible towards the norm of a small happy and prosperous family. contraception and provide free contraceptive installation services. The result of this service is that the client understands the benefits of using contraceptives and is willing to using contraceptives Keywords : Counseling, Family Planning, Using of Contraceptive Devices